Slum an Urban Tourism Resource in Zambia. A case study of Kalingalinga Informal Settlement, Lusaka - OLATUNBOSUN SANUSI (2021)
Slum settlements are often reviewed as urban spaces of social complexity where people are often ensnared in a poverty trap. Conversely, slum spaces are exploited as a resource by multiple stakeholders and poverty is an attraction. Pro-poor slum tourism is being utilised in slum settlements outside Zambia as a tool for capacity building, utilising slum dwellers’ resilience, ingenuity, uniqueness and entrepreneurial spirit. This explorative study adopts a qualitative approach in investigating Kalingalinga settlement in Lusaka, Zambia and begins by observing the space through participating in a slum tour. This is followed by interviews with multiple stakeholders, through which participants understanding and perception of the concept of slum tourism are reviewed. Investigation revealed that Kalingalinga is a space of poverty and basic infrastructure, threatened by demand for its location. The informal space is constantly changing and redefining its position within society, fighting for recognition and acceptance. Analysis revealed that this interaction leads to exploitation of slum resources that mainly benefit external stakeholders. A new approach is proposed; to redefine interactions and relationships, to address the root of poverty, and the slum’s informal status. This research, through a conceptual framework for slum tourism, identifies means through which poverty could be exploited by Kalingalinga slum dwellers as a resource for inclusion and, through a pro-poor approach, generate net benefit that satisfies all stakeholders. A key finding suggests that slum spaces could be navigated through a relative slum tourism approach (RST) rather than absolute slum tourism commonly adopted by slum tourists. RST allows the tourist to witness wider activities slum dwellers are involved in, extending the narrative beyond the confines of the settlement. To achieve sustainability, the framework suggests that the people, rather than the location, should be placed at the centre of pro-poor slum tourism and community development.